Libyan Students’ Perceptions towards Extracurricular Activities in Learning English as a Foreign Language: A Study at the Department of English at Sirte University - Nouriya Elsaadi; Yousuf Ahfaf (Abhat Journal, 2025)
The aim of this study was to find out the perceptions of Libyan students on extracurricular activities (ECAs) in learning English as a foreign language in the English Department at Sirte University. An adapted questionnaire (close and open-ended questions) was used to collect the data for the study. An online survey questionnaire was conducted with 60 respondents who were selected anonymously. The data of the close-ended questions was analyzed by Google Form whereas the data from open-ended questions was analyzed thematically. The findings revealed that the majority of participants tend to have positive perception towards ECAs in terms of their academic performance, in helping them achieve better grades. ECAs also developed students’ skills, and motivated them, as well as helping them become more organized. On the other hand, some participants claimed that ECAs constitute extra burden and distraction from their main academic assignments. The study concludes with some pedagogical recommendations and suggestions for further research.